Hypothyroidism has a protective causal association with hepatocellular carcinoma: A two-sample Mendelian randomization study - Lu, Likui; Wan, Bangbei; Li, Lingjun; Sun, Miao (Frontiers in Endocrinology, 2022)
Objective Observational studies suggest an association between hypothyroidism and the risk of hepatocellular carcinoma (HCC), but the causality and direction of these effects are still inconclusive. We aim to test whether hypothyroidism is causally associated with the risk of HCC by using Mendelian randomization (MR) analysis. Methods Single-nucleotide polymorphisms (SNPs) associated with hypothyroidism were screened via a genome-wide association study (GWAS) on 337,159 individuals of European descent (16,376 cases and 320,783 controls). The SNPs associated with thyroid-stimulating hormone (TSH) and free thyroxine (FT4) were selected from a GWAS of 72,167 individuals of European descent. Summary-level data for HCC (168 cases and 372,016 controls) were extracted from UK Biobank. An inverse-variance-weighted (IVW) method was used as the primary MR analysis. Sensitivity analyses were examined via MR-Egger regression, heterogeneity test, pleiotropy test, and leave-one-out sensitivity test. The assumption that exposure causes outcome was verified using the MR Steiger test. Results Two-Sample MR analysis showed inverse associations between genetically predicted hypothyroidism and HCC risk (OR = 0.997, 95% CI, 0.995-0.999; P = 0.016). There were no statistical indications of heterogeneity among instruments (P-het = 0.667). Across five MR methods, genetically predicted hypothyroidism shows a consistent correlation with HCC. The leave-one-out analysis indicated that no single SNP changed the overall estimate (P = 0.016). In addition, the MR Steiger test revealed that hypothyroidism was causal for HCC and not the opposite (P = 0.000). Finally, there was no evidence for a direct causal effect of TSH level and FT4 level on HCC risk. Conclusion Our results provide some that genetically determined hypothyroidism decreases the risk of HCC, although the size of the causal estimate is small. Further research is required to comprehend the mechanisms underlying this putative causative association, and follow-up clinical trials need to be conducted to establish whether inducing hypothyroidism could be beneficial for patients who are suffering from HCC. During future treatment of hypothyroidism, close attention to liver function may also be required to prevent a possible increased risk of HCC.